2016
DOI: 10.1002/isaf.1400
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Entrepreneurship at the Base of the Social Pyramid via Pricing Systems: A case Study

Abstract: Summary Historically, microfinance institutions (MFIs) have played a significant social role by helping people at the base of the socio‐economic pyramid escape from social exclusion through the creation of microenterprises. However, international banks have recently started competing in the microfinance sector. In this adverse environment, MFI management tools should be more innovative and technologically advanced to increase efficiency, solvency and profitability and to compete with commercial banks on equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
(54 reference statements)
3
8
0
Order By: Relevance
“…As explained in the first section, both the recommendations of international bodies and the conclusions of previous research (Navarro et al, 2020;Lara-Rubio et al, 2017;EU, 2015;IMF, 2015;World Bank, 2014;Elgin & Uras, 2013;Castro, 2013;Schularick & Taylor, 2012) have highlighted the urgent current need to incorporate systemic factors into the analysis of default risk, thus improving on the traditional approach based on idiosyncratic factors alone. In this respect, variables such as GDP (real gross domestic product) and COLCAP (the main stock market index of the Colombia Stock Exchange) may exert a direct influence on PD (Shahriar et al, 2016;Shahriar & Garg, 2017;Zafra-Gómez, López-Hernández, & Hernández-Bastida, 2009).…”
Section: Systemic Variablesmentioning
confidence: 99%
“…As explained in the first section, both the recommendations of international bodies and the conclusions of previous research (Navarro et al, 2020;Lara-Rubio et al, 2017;EU, 2015;IMF, 2015;World Bank, 2014;Elgin & Uras, 2013;Castro, 2013;Schularick & Taylor, 2012) have highlighted the urgent current need to incorporate systemic factors into the analysis of default risk, thus improving on the traditional approach based on idiosyncratic factors alone. In this respect, variables such as GDP (real gross domestic product) and COLCAP (the main stock market index of the Colombia Stock Exchange) may exert a direct influence on PD (Shahriar et al, 2016;Shahriar & Garg, 2017;Zafra-Gómez, López-Hernández, & Hernández-Bastida, 2009).…”
Section: Systemic Variablesmentioning
confidence: 99%
“…Additionally, Lara‐Rubio et al . () compared an MLP credit‐scoring model and an LR model under the Basel II internal ratings‐based (IRB) recommendations, for a Peruvian microfinance institution. They showed that the MLP‐IRB model performed better than the LR‐IRB model with important implications for microfinance institutions in terms of improving their profitability and efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the crisis escalates, the SVM model performs better than the other models, followed by the DT and then the MLP. Our study contributes to the existing credit‐scoring literature for SMEs' delinquencies (Wu & Wang, ; Bensic et al ., ; Abdou, El‐Masry, & Pointon, ; Crook, Edelman, & Lyn, ; Mileris & Boguslauskas, ; Louzada, Ferreira‐Silva, & Diniz, ; Lara‐Rubio et al ., ; Sun & Vasarhelyi, ) with important implications for bank management and policy‐makers. The rest of the paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of Web 2.0 and social networks in business models and financing methods has led to dramatic changes in start-up businesses and innovative entrepreneurs. One of these changes has occurred through the emergence of crowd funding in the field of financing [8]. Crowd funding is rooted in crowdsourcing and has been extracted from outsourcing.…”
Section: Introductionmentioning
confidence: 99%
“…Crowd funding can be considered to have originated from three scientific fields. The first is financial management, which is a microfinance entity [2,8,20]. According to the definition provided in Britannica Encyclopedia, microfinance is a means of extending credit, usually in the form of small loans with no collateral, to nontraditional borrowers such as the poor in rural or undeveloped areas [21].…”
Section: Introductionmentioning
confidence: 99%